Aplikasi Pengelola Tamu Wedding berbasis Mobile Android - Winata Sukiman; Agustinus Noertjahyana; Anita Nathania Purbowo (Jurnal Infra, 2019)
In a wedding there must be guests who have been invited by the person who has the wedding event. It is clear that the presence of the guest is very important because it supports in enlivening the wedding. Of course, guests who have been invited by the bride and groom are guests who are highly expected to attend the wedding. When we invite guests to attend a wedding, it is necessary to share the invitation to let them know that they will be invited to attend the wedding.In this thesis, a guest management application based on mobile android will be created. The guest manager in question is managing guests in terms of sending invitations and reception. Delivery of invitations through the application is done by sending an invitation via e-mail. The wedding invitation also contains applications that must be downloaded guests because in the application there is a qr code as a marker of guest identity. In addition, if there is a door prize, then drawing or taking door prize winners is done in the application. In the application there is also a wedding schedule and there is a google maps direction if there are troubled guests looking for the location of the wedding. While in terms of reception is done by doing a scan there is a qr code that is in the application. So that when the guest comes, only with the qr code, the guest identity can be known. If the guest forgets to download the application then guest searches can be based on names.The final result of this thesis is the guest management application can help in sending wedding invitations and help reduce the queue that is available at reception.